Manajemen Akhlak Peserta Didik di Era Modernisasi Teknologi Informasi - Muhasim Muhasim (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2019)
National education functions to develop capabilities and form, dignified national character and civilization in order to educate the nation's life, aiming at developing potential students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become a democratic and responsible citizen. Such is the importance of noble character, so that guidance must continue to be carried out at a minimum along with the modernization of information technology. Noble character according to the term especially in Islam as a believer is defined as the nature or temperament of someone who has been attached and will usually be reflected in the behavior of that person. Someone who has good character will usually have good temperament or character too and vice versa someone who has a bad temper tended to have despicable character. There is no noble character for people who are not believers, so there is no faith for people who are despicable, because only people of noble character are able to avoid despicable deeds. But the reality of life still occurs behavior that is contrary to noble morals, such as those who relieve performing prayer, perform other acts of corruption: corruption, extortion, embezzlement, murder and turn am ong students still occur From the description above we observe that there are still many incompatibilities between moral values, with the attitudes and behavior of some people, including students. Therefore, noble moral formation is still needed, and for this purpose management intervention is still very important. The method used is descriptive method, which means understanding what is the object of writing, looking at various situations or social realities that exist in society from various sources that can be trusted, writing on online media is the subject of discussion. The results expected in this paper are to create a generation that is trustworthy, consistent, patient and trustworthy, in entering the era of information technology modernization, and able to avoid the negative influence of information technology. Therefore community development, including students to have noble character, is a necessity, because only in this way can the national education mandate be created, namely creating the potential of students to become human beings who believe and fear the Almighty God, have noble character, are healthy, knowledgeable , capable, creative, independent, and a democratic and responsible citizen.